2011
DOI: 10.1016/j.antiviral.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Combination of α-glucosidase inhibitor and ribavirin for the treatment of dengue virus infection in vitro and in vivo

Abstract: Cellular α-glucosidases I and II are enzymes that sequentially trim the three terminal glucoses in the N-linked oligosaccharides of viral envelope glycoproteins. This process is essential for the proper folding of viral glycoproteins and subsequent assembly of many enveloped viruses, including dengue virus (DENV). Imino sugars are substrate mimics of α-glucosidases I and II. In this report, we show that two oxygenated alkyl imino sugar derivatives, CM-9-78 and CM-10-18, are potent inhibitors of both α-glucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 33 publications
1
100
0
1
Order By: Relevance
“…This impressive SI is largely due to the low cytotoxicity observed in this assay-a result consistent with the current safe use of NB-DNJ in humans. Other DNJ derivatives with more potent antiviral activity than NB-DNJ (shown in studies by ourselves and others) (7,9,36) generally show greater toxic effects on cells in vitro. In support of this trend, the cytotoxicity of the four iminosugars we tested (NB-DNJ, NN-DNJ, N9-MON-DNJ, and NAP-DNJ) was correlated with antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This impressive SI is largely due to the low cytotoxicity observed in this assay-a result consistent with the current safe use of NB-DNJ in humans. Other DNJ derivatives with more potent antiviral activity than NB-DNJ (shown in studies by ourselves and others) (7,9,36) generally show greater toxic effects on cells in vitro. In support of this trend, the cytotoxicity of the four iminosugars we tested (NB-DNJ, NN-DNJ, N9-MON-DNJ, and NAP-DNJ) was correlated with antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
“…In trials as an anti-HIV therapy, administration of free drug did not sustain sufficiently high serum concentrations to achieve an antiviral effect (14). Since that time, iminosugars with improved in vitro potency (but concurrently greater cellular toxicity) have been developed (1,7,9,16,24,33). As a parallel approach to enhance NB-DNJ potency, liposome-mediated intracellular delivery of iminosugars shows great promise (30).…”
mentioning
confidence: 99%
“…These results strongly argue that, unlike drugs targeting viral functions, inhibition of host cellular functions essential for HCV replication, such as ␣-glucosidases, has a low likelihood of developing resistant mutants. This unique property, in combination with much-improved antiviral efficacy, makes PBDNJ0804 a promising antiviral candidate for combination therapy with IFN-␣ or drugs that inhibit viral functions (7).…”
Section: Discussionmentioning
confidence: 99%
“…Compounds that disrupt glycosylation can cause viral glycoproteins to misfold, ultimately resulting in reduced assembly, secretion, and infectivity of viral particles (17,18). Iminosugars are monosaccharides that target the host enzymes ␣-glucosidase I and II (19,20). It has been shown that iminosugars affect the folding of the prM protein of DENV and subsequently the formation of the prM-E complex (21).…”
mentioning
confidence: 99%